The place of volition in addiction: Differing approaches and their implications for policy and service provision - Karasaki, M.; Fraser, Suzanne; Moore, David; Dietze, P. (Wiley-Blackwell Publishing Ltd., 2013)
Introduction: ‘Addiction’ is an ambiguous concept. Its meaning, and how it is used in drug policy and treatment, depends on how it is conceptualised. While the ‘disease’ model of addiction is prevalent in Australia, differing, sometimes contradictory, interpretations of this model are mobilised.Methods: Drawing on 20 semi-structured interviews conducted with professionals working in the area of drug use in Victoria, Australia, this paper develops a typology delineating different approaches to addiction.Results: Five domains of meaning related to addiction were identified in the data. These were: (i) the sign of craving; (ii) susceptibility; (iii) social and psychological issues producing addiction; (iv) self-concept; and (v) social functions of addiction. These domains are further divided into two subtypes based on how the participants understood the role of a key notion in addiction: volition, that is, whether or not an ‘addict’ has control over drug use and other aspects of life.Discussion: By systematically mapping different conceptualisations of addiction, this typology identifies the ambiguities and contradictions in the models currently in use, especially with respect to the notion of volition. While a homogeneous approach to these issues is neither practical nor desirable, there is a need to consider the implications of this lack of coherence.Conclusions: Service providers, medical practitioners and policy makers need to reflect on their assumptions, and consider the implications of their different approaches for clients, some of whom encounter more than one approach when undergoing treatment for drug use.